Media and Religion: Study of Anti-Shi’a Propaganda in Yogyakarta - Anang Masduki; Panqiang Niu; Agus Triyono (Komunikator, 2021)
Some time ago, a rift arose between Sunnis and Shiites in Sampang, Madura. Then, banners spread across Yogyakarta stating that the Shia were heretical. On the internet, many websites sprang up claiming that anyone that justifies Shia is heretical. These were a form of propaganda, campaigning, or “proselytizing” that another group is deviant and infidel. This research tried to analyze the propaganda process in the media by radical groups against Shiite groups in Yogyakarta and to find out the techniques and tools used in it so that all parties could anticipate and map the potential conflicts. The research was conducted in Yogyakarta with a qualitative research type. Data collection was carried out by document review. The results showed that, first, propaganda provided a stimulus to the public to seek knowledge and information about the Shi’a group –and mainly conveyed a negative view of the Shi’a group. Second, this research found that the mechanism carried out was by providing information to the public by placing the media in strategic places. Third, the research identified that the propaganda theory used is Name-Calling, Glittering Generality, and Transfer, while the media used were billboards, banners, leaflets, and brochures.